The concrete structure remedial assessements in marine environment from whole life asset management perspectives - Mohd Salleh, Mohd Rezal (2008)
This study makes use of a desk top review methodology to discover and understand the remedial assessment of damage concrete structures in the marine environment (sea water). Basically, the restorations of asset marine facility are done by using a correct and present repair technique to both spall concrete as well as corrode rebar and must follow the code and standards throughout construction periods. Specifically, the study undertook a comprehensive insight into the literature review of three (3) major components of research, consisting of reinforced concrete of marine structure, understanding marine environment and management of rehabilitation marine facility. The research chooses a case study of an oil refinery jetty piles terminal at Marsden Point in New Zealand. The asset facility is poorly deteriorating due to aggressive action of marine environment and need attention. The asset owners are aim to establish potential maintenance strategies in restoration of his asset facilities. The damaged marine structure will be looked at from whole life asset management perspectives; to identify various components of concrete structures that were subjected to steel corrosion and concrete deterioration. Application of whole life asset management paradigm in the case study will have significant impacts to the facilities and the owner as well. The benefits with regard to implementation of whole life asset management approaches in managing the asset marine facility correlate with risk management, accountability, service facility management and financial efficiency. The refurbishment work will make use of current repair method in assessing the restoration of damage concrete piles. This should take account of a risk management study prior selection of best procurement routes for the case studies. The case study is critically reviewed for options that suit the asset facility present condition and set up objectives to get the best approach adopted with regards to asset problem. The findings demonstrate that the adoption of the whole life asset management paradigm will promote the asset owner, to obtain best value for money concept from the investment and to gain benefits in terms of time, cost, quality and fit for purpose. It also help in promoting and prolong the asset lifespan and also to provide constant sustainable and economic service of asset facilities.